2016
DOI: 10.1007/s11845-016-1412-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and registration as drivers of continuous professional competence for Irish pre-hospital practitioners: a discussion paper

Abstract: Background The Regulatory Body responsible for the registration of Irish pre-hospital practitioners, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…They further suggest that for professionalism to exist paramedics must believe that their work is unique, requiring it to be underpinned by a unique body of knowledge and educational processes (46). Bowles, Newton and Hodge, and Knox et al highlight the importance of education in building professionalism (37,47,48). The challenge of incorporating professionalism into curricula is discussed given the transient, situational and subjective nature of professionalism.…”
Section: Paramedic Professionalismmentioning
confidence: 99%
See 1 more Smart Citation
“…They further suggest that for professionalism to exist paramedics must believe that their work is unique, requiring it to be underpinned by a unique body of knowledge and educational processes (46). Bowles, Newton and Hodge, and Knox et al highlight the importance of education in building professionalism (37,47,48). The challenge of incorporating professionalism into curricula is discussed given the transient, situational and subjective nature of professionalism.…”
Section: Paramedic Professionalismmentioning
confidence: 99%
“…The challenge of incorporating professionalism into curricula is discussed given the transient, situational and subjective nature of professionalism. It is noted that while foundational education lays the groundwork for core professional practice, continuing education is a significant driver in professionalisation (48). If viewed in the context of Burford et al, professionalism is the capacity to make situational decisions based against a social and professional context.…”
Section: Paramedic Professionalismmentioning
confidence: 99%
“…Continuing competency mechanisms vary across jurisdictions and practitioner groups in the same jurisdiction. These mechanisms include mandatory CPD standards required to renew registration [ 166 168 ], certification and recertification programs run by a range of non-government bodies [ 122 , 169 171 ], maintenance of certification programs run by specialist colleges [ 172 177 ], and revalidation programs run in partnership between regulators and employers [ 131 , 178 , 179 ]. Requiring participation in CPD is the most common mechanism used by regulators to assure the continuing competence of registrants.…”
Section: Resultsmentioning
confidence: 99%
“…The second group of papers reported that continuing professional development (CPD) was generally appreciated and valued [44][45][46][47]. CPD is now increasingly widespread and mandatory in the health and care professions [48].…”
Section: Education and Trainingmentioning
confidence: 99%